2022
DOI: 10.3390/molecules27196740
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Effects of Cannabidiol against Ultraviolet-B-Induced DNA Damage and Autophagy in Human Keratinocyte Cells and Mouse Skin Tissue

Abstract: Cannabidiol (CBD) has emerged as a phytocannabinoid with various beneficial effects for the skin, including anti-photoaging effects, but its mechanisms of action are not fully elucidated. The study assessed CBD’s photoprotective effects against acute ultraviolet B (UVB)-induced damage in HaCaT human keratinocyte cells and murine skin tissue. CBD (8 μM) alleviated UVB-induced cytotoxicity, apoptosis, and G2/M cell cycle arrest in HaCaT cells. The contents of γH2AX and cyclobutane pyrimidine dimers were decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Conversely, the PPARγ receptor plays a role in modulating inflammatory signaling by inducing the p65 subunit of the NF-κB transcription factor [ 38 ]. Consequently, the obtained results validate previous reports of increased oxidative stress and inflammatory responses in UVB-exposed keratinocytes [ 28 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, the PPARγ receptor plays a role in modulating inflammatory signaling by inducing the p65 subunit of the NF-κB transcription factor [ 38 ]. Consequently, the obtained results validate previous reports of increased oxidative stress and inflammatory responses in UVB-exposed keratinocytes [ 28 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, keratinocytes exposed to UVB radiation and then exposed to microalgae show a reduction in the level of phospholipid peroxidation products. However, considering that proteins and partly DNA can also undergo structural and functional changes under the influence of UVB radiation [31], the regenerative effect of algae can also be indicated to proteins, which was also observed in previous studies [34].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For the CBD-NLCs, cell viabilities higher than 90% were observed for concentrations less than or equal to 12.8 µg/mL, corresponding to 11.14 μg/mL or 35.41 µM. The cytotoxicities of CBD on HaCaT and HDF cells have been reported in several studies, while the reported CBD concentrations that were not toxic to HaCaT and HDF cells were different in each study [ 2 , 47 , 48 , 49 , 50 , 51 ]. For example, the study by Sangiovanni et al indicated that CBD concentrations higher than 2.5 μM were toxic to HaCaT and HDF cells [ 47 ], whereas Petrosino et al reported that treatment of HaCaT cells with 20 μM CBD did not cause toxicity to cells [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wondrak et al [122] reported that photosensitization by both endogenous and synthetic 3-hydroxypyridine derivatives inhibited the proliferation of cultured human skin keratinocytes and fibroblasts and induced their apoptosis in a dose-dependent manner. In an independent study, Li et al [123] found that cannabinol effectively inhibited UVB-induced cytotoxicity, apoptosis, and G2/M cell cycle arrest in human keratinocytes by modulating autophagy. In addition, cannabinol counteracted aberrant cell proliferation in UVB-exposed photodamaged mouse skin and suppressed the expression of cyclooxygenase-2 protein, thereby improving the overall skin condition.…”
Section: Resultsmentioning
confidence: 99%